Alpha6-Containing Nicotinic Acetylcholine Receptors Mediate Nicotine-Induced Structural Plasticity in Mouse and Human iPSC-Derived Dopaminergic Neurons - Collo, Ginetta; Cavalleri, Laura; Zoli, Michele; Maskos, Uwe; Ratti, Emiliangelo; Merlo Pich, Emilio (Frontiers in Pharmacology, 2018)
Midbrain dopamine (DA) neurons are considered a critical substrate for the reinforcing and sensitizing effects of nicotine and tobacco dependence. While the role of the α4 and β2 subunit containing nicotinic acetylcholine receptors (α4β2∗nAChRs) in mediating nicotine effects on DA release and DA neuron activity has been widely explored, less information is available on their role in the morphological adaptation of the DA system to nicotine, eventually leading to dysfunctional behaviors observed in nicotine dependence. In particular, no information is available on the role of α6*nAChRs in nicotine-induced structural plasticity in rodents and no direct evidence exists regarding the occurrence of structural plasticity in human DA neurons exposed to nicotine. To approach this problem we used two parallel in vitro systems, mouse primary DA neuron cultures from E12.5 embryos and human DA neurons differentiated from induced pluripotent stem cells (iPSCs) of healthy donors, identified using TH+ immunoreactivity. In both systems, nicotine 1-10 μM produced a dose-dependent increase of maximal dendrite length, number of primary dendrites and soma size when measured after 3 days in culture. These effects were blocked by pretreatments with the α6*nAChR antagonists α-conotoxin MII and α-conotoxin PIA, as well as by the α4β2 nAChR antagonist dihydro-β-erythroidine (DHβE) in both mouse and human DA neurons. Nicotine was also ineffective when the primary DA neurons were obtained from null mutant mice for either the α6 subunit or both the α4 and α6 subunits of nAChR. When pregnant mice were exposed to nicotine from gestational day 15, structural plasticity was also observed in the midbrain DA neurons of postnatal day 1 offspring only in wild-type mice and not in both null mutant mice. This study confirmed the critical role of α4α6∗nAChRs in mediating nicotine-induced structural plasticity in both mouse and human DA neurons, supporting the translational relevance of neurons differentiated from human iPSCs for pharmacological studies.